Tabu, hambatan budaya pendidikan seksualitas dini pada anak - Ratna Zakiyah; Yayi Suryo Prabandari; Atik Triratnawati (Berita Kedokteran Masyarakat (BKM), 2016)
Taboo, the culture’s barrier of early sexuality education for children in the city of DumaiPurposeThe study aimed to excavate the perception of parents against early sex education for children. It will provide information about the best intervention measures through sex education.MethodThe study used a descriptive exploratory study with a qualitative approach. Selection of research subjects was done by purposive sampling. Data were collected by focus group discussion (FGD) and in-depth interviews. The analysis being used was content analysis.ResultsKnowledge of parents in cases of children sexual abuse (CSA) was still minim. The main barrier factors that prevent parents providing sexuality education in early childhood were an inconvenience-felt, the perception of the child unpreparedness and nescience of how to deliver sexuality education in children. The availability of adequate information about sexuality, good communication and the role of fathers in sexuality education will facilitate the parents in providing sexuality education in early childhood.ConclusionParents need to get more socialization of SVC cases that occurred in the city of Dumai. Health promotor should be able to take advantage of the forums that involve parents, such as posyandu or school committee meeting, to promote early appropriate sexuality education for children.